2011
DOI: 10.1007/s00134-011-2352-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurally triggered breaths reduce trigger delay and improve ventilator response times in ventilated infants with bronchiolitis

Abstract: Neurally triggered breaths reduce trigger delay, improve ventilator response times, and may decrease work of breathing in children with bronchiolitis. Further analysis is required to determine if neurally triggered breaths will improve patient-ventilator synchrony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…In line with the expectations of its fundamental principle, NAVA has in over 10 clinical studies been shown to decrease (and in several studies almost eradicate) patient-ventilator asynchrony, in comparison to other modes of ventilation [Alander et al 2012;Beck et al 2009;Bengtsson and Edberg, 2010;Breatnach et al 2010;Cammarota et al 2011;Clement et al 2011;Colombo et al 2008;de la Oliva et al 2012;Moerer et al 2008;Piquilloud et al 2011;Spahija et al 2010;Terzi et al 2010]. Based on these results, the relationship between NAVA and improved synchrony is well established.…”
supporting
confidence: 61%
“…In line with the expectations of its fundamental principle, NAVA has in over 10 clinical studies been shown to decrease (and in several studies almost eradicate) patient-ventilator asynchrony, in comparison to other modes of ventilation [Alander et al 2012;Beck et al 2009;Bengtsson and Edberg, 2010;Breatnach et al 2010;Cammarota et al 2011;Clement et al 2011;Colombo et al 2008;de la Oliva et al 2012;Moerer et al 2008;Piquilloud et al 2011;Spahija et al 2010;Terzi et al 2010]. Based on these results, the relationship between NAVA and improved synchrony is well established.…”
supporting
confidence: 61%
“…2 Adult and pediatric studies showed that NAVA increases breath-to-breath variability and improves patient-ventilator synchrony and patient comfort. [3][4][5][6][7][8][9] This last improvement is also effective in NIV in adult and pediatric subjects 10,11 and in very low birthweight infants, even in the presence of large leaks. 12 To our knowledge, no previous study was designed to evaluate this ventilation mode exclusively in the postoperative period after cardiac surgery in newborns.…”
Section: Introductionmentioning
confidence: 97%
“…NAVA delivers mechanical assistance in proportion to patient effort, allowing the tailoring of the mechanical support to patient' respiratory characteristics. Several studies 15,[22][23][24][25][26] showed that NAVA is a safe and reliable mode in the pediatric and infant population. It improved synchrony and patient comfort, reduced ventilator drive, and increased breath-tobreath mechanical variability.…”
Section: Discussionmentioning
confidence: 99%